FORMULASI GEL EKSTRAK KULIT BUAH NAGA MERAH SEBAGAI TABIR SURYA - Ira Oktaviani Rz; Dian Novita; Fathul Jannah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
Sunscreen is a preparation that contains chemical compounds that can absorb, scatter or reflect sunlight that hits the skin so that it can be used to protect the function and structure of human skin from damage caused by sunlight. In the field of pharmacology, dragon fruit peel can be used as an antioxidant or free radical scavenger. This study aims to determine the SPF value of red dragon fruit (Hylocereus lemairei (Hook) Britton & Roose) peel extract and gel at concentrations of 30%, 50% and 70%. This research is a quantitative descriptive analysis. Red dragon fruit peel extract was tested using the Uv-Vis spectrophotometry method. The results showed that the SPF value of the red dragon skin extract was 13.0225; the SPF value of red dragon fruit peel extract gel at concentrations of 30%, 50%, and 70% were 5.1557; 8.5413; and 6.8113. Where the extract from the red dragon fruit skin has good potential if used as an active ingredient in gel preparations to protect against ultraviolet light because each concentration has an SPF value with the category of extra sunscreen protection (6-8) and maximum protection (8-15).